Interactions between stakeholders in Lourdes: An `Alpha' framework approach - Hugues Séraphin; Nathalie Jarraud (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: Taking Lourdes as an en example, this paper aims at understanding the relationship amongst the main tourism and events industry stakeholders. Methods: To achieve the objective of the study, data were collected through interviews of key players. The results where then filtered through the 'Alpha' framework to theorise the interactions amongst stakeholders. Results: The study also provides a (1) typology of the ultimate alpha syndrome in the context of destination management; (2) typology of the delta syndrome. (3) Finally, the study argues that in destinations where there is an ultimate alpha hallmark event, or an ultimate alpha stakeholder, a situation quite similar to an anti-competitive market can arise. This situation is referred as 'ultimate alpha tourism monopoly'. Implications: Based on the findings of this study, Destination Marketing Organisations need to ensure that there is a suitable synergy amongst all stakeholders involved in the tourism industry (and related sector), to avoid anti-competitive market 'ultimate alpha tourism monopoly' to arise.
Keywords: O52; Z3; L1; 330; Alpha framework; Destination management; Hallmark